The colonial face of 'housing' refugees: the construction of the racialised subject within a necropolitical infrastructure - Astolfo, Giovanna; Allsopp, Harriet (Housing studies, 2025)
The incredible mobilisation to welcome Ukrainian refugees following the start of the Russia-Ukraine war in 2022 demonstrated how housing is an affective sociomaterial infrastructure. In cruel contrast, such mobilisation also exposed the inherently racist and colonial face of accommodating refugees and migrants, and the structural inequalities that racial capitalism continues to reproduce. Drawing reflections across several geographies and temporalities through illustrative vignettes, this paper begs the questions under what conditions do we accept that some people are housed, others not? What kind of power structures allow certain bodies to be welcomed? This paper borrows from postcolonial, black and critical theory to examine refugee housing through the lens of necropolitical infrastructure. It connects Mbembe's notion of necropower with Power and Mee's notion of housing as infrastructure of care, and filters this through reflections across Calais, Brescia and Athens, to illustrate the bio- and necropolitical side of the refugee housing infrastructure in Europe. The paper ultimately argues that refugee housing, because it is an infrastructure and because it is part of the broader extractive and exploitative system of (humanitarian) care, is deeply imbricated in the production of racialised subjects. Specifically, it is complicit with the extraction, (re)incorporation, abandonment and slow death of Black and Brown refugee lives.